A culpabilidade como fator de delimitação da pena - Roversi Júnior, Antonio (2015)
This study aims to analyze the culpability as the delimitation factor in the first phase of the three-phase criterion for the application of criminal penalties. To this end, the culpability is considered according to its different aspects: as a constitutional principle derived from the foundation of the dignity of the human person, as an element of the delict structure and as a factor of delimitation of the penalty. Based on the historic construction of the institute, it is noted that the culpability constitutes a penalty limiting factor to be imposed when a delict is committed, not allowing to differentiate their material content as a structuring element of the delict nor as an individualization element of its punishment. This is so because, even when analyzed under the latter aspect, the penalty is also susceptible to gradation, and this extent will greatly influence the quantification of the applicable penalty, being the differentiation of those two concepts an undesirable measure which results in an enlargement of its content, allowing an expansion of the state s punishing power. Even if allocated under the diction of article 59 of the Brazilian Penal Code alongside other circumstances, culpability should be held in a prominent position, not assuming the same level of other elements, so to establish a maximum limit to the penalty and prevent other circumstances from exceeding such limitation